2021
DOI: 10.1186/s12889-021-11788-4
|View full text |Cite
|
Sign up to set email alerts
|

Explaining utilization of HIV prevention and testing services among university students in Mozambique: results from a mixed methods study

Abstract: Background In Mozambique, HIV infection disproportionately affects young adults, particularly women. Despite awareness and knowledge of HIV transmission, many university students have not received HIV testing and continue to engage in high-risk sexual behaviors, including inconsistent condom use. Further understanding of patterns of engagement with HIV prevention and testing is key to reducing HIV transmission in this at-risk population. Methods Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 38 publications
3
3
0
Order By: Relevance
“…Lack of privacy when handling sensitive information has been considered to be a glitch of privacy. These research findings were consistent with two other studies done in Nigeria and Mozambique [17,18]. Study respondents who reported being counseled to bring families for HIV testing were 1.9 times more expected to utilize community HIV index testing as linked to their colleagues.…”
Section: Discussionsupporting
confidence: 90%
“…Lack of privacy when handling sensitive information has been considered to be a glitch of privacy. These research findings were consistent with two other studies done in Nigeria and Mozambique [17,18]. Study respondents who reported being counseled to bring families for HIV testing were 1.9 times more expected to utilize community HIV index testing as linked to their colleagues.…”
Section: Discussionsupporting
confidence: 90%
“…Compared with a study conducted in a similar setting in TVET colleges in a rural and urban province in South Africa, 72% of students indicated that they have been previously tested for HIV which is comparable to our findings [21]. This result is higher than that found by studies conducted among university students in other countries [25,27,37]. Additionally, our quantitative results show that there are differences in perceived use of HCT services between females and males.…”
Section: Discussionsupporting
confidence: 77%
“…Moreover, HIV testing remains the most critical intervention to HIV prevention and entry into continuum of care for those who test positive. Although previous studies argue that higher education is protective, and students are more likely to have been tested for HIV [22,23], this is in contrast to similar studies conducted in the region were the majority of students reported that they were sexually active and most of their sexual encounters were unprotected [18,19,24,25]. Additionally, previous studies conducted revealed that university students engage in sexual encounters while intoxicated [22,26] and often do not take precautionary measures to reduce HIV infections such as using condoms correctly and consistently [27][28][29].…”
Section: Introductionmentioning
confidence: 62%
See 2 more Smart Citations